Students’ perception of the use of “Rebus Game Puzzle” to improve speaking skills of eighth-grade students - Pramesti, Magdalena Ayu Sri; Sulistyani, Ummi Nur Laila (Universitas Negeri Semarang, 2025)
The study aimed to determine what students think about the Rebus Game Puzzle as a medium for learning English, particularly in improving speaking skills. Common problems include students lacking confidence, having a limited vocabulary, and rarely speaking actively in class. Therefore, learning media such as Rebus Puzzle are used to help overcome these problems. This study used interviews with eighth-grade students and English teachers at a private junior high school in Central Java. The results showed that the Rebus Puzzle helps students remember vocabulary more easily and practice their pronunciation. The pictures and instructions in the puzzle make students more interested and less likely to be bored. In addition, the learning atmosphere becomes more engaging, allowing students to be more active, confident, and brave in speaking in front of the class. Therefore, it is recommended that teachers utilize game media, such as Rebus Puzzle, in the learning process, especially when teaching vocabulary and speaking. This media can make students more enthusiastic and make learning more meaningful. whether media such as Rebus Puzzle could increase students' enthusiasm, activity, and confidence while learning English.